The performance of Islamic mutual funds, why is it not better than conventional? - Faaza Fakhrunnas (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
The Islamic mutual funds objective tries to safeguard the moslem community from usury, masyir, and gharar. However, that product still has a problem which relates to the performance. Based on the literature review, Islamic mutual funds can not outperform the market benchmark and the conventional mutual funds. It happens because of some factors in the Islamic mutual funds product. Unskilled manager is the inside factor causing the lack of Islamic mutual funds performance. It is because the manager does not have many choices in making portfolio aligned with shariah. Then, the outside factor is about the regulation itself relating to the goverment policy. In this paper, the writer tries to offer the solutions. Firstly, Islamic mutual funds has to be bravely different to give clear identity as fully shariah compliance in purpose to attract moslem communities to invest. Secondly, the goverment has to promote Islamic funds market to make it more developed.